La professionnalisation des formations supérieures : facettes multiples et effets incertains - José Rose
This text proposes a definition of the professionalization notion since the moving context of universities. The author discusses the impact off the transformations on student's paths and their professional insertion. He offers a more complex professionalization definition based on the notion of professionalism that permits skills adaptation to the changing job' activities. This text engages the debate about the content of professionalization. It underlines the impact of internships, vocational sandwich courses, and job market realities. Finally the author argues that is an interconnexion between enterprise behaviors, realities of job markets, and the quality of the training which define the success of the professionalization training process.